PENGELOLAAN BUDAYA SEKOLAH DALAM MENCEGAH POTENSI PENYIMPANGAN SEKSUAL DI KALANGAN PESERTA DIDIK SDN 57 BANDA ACEH - Sumbayak, Rizky; Mutia, Sri; Sari Sumbayak, Mega (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School culture is a system of values, norms, and habits in shaping the behavioral character of students. The research uses a qualitative descriptive approach using data collection techniques through interviews, observations, and documentation.as for the research informants, 4 people consist of the principal, homeroom teachers of grades 4, 5, and 6. Data was analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data was carried out through triangulation of sources and techniques. The results of the study show that school culture management is carried out through habituation of religious values, strengthening discipline, character education, supervision of student behavior, and harmonious communication between schools and parents. The results of the study show that school culture functions to shape the behavior of school residents through values and traditions that are applied consistently. In addition, the results of the study also show that a positive school culture is able to strengthen students' social control so that they can minimize deviant behavior from an early age even though the influence of digital media and limited supervision outside school are still challenges in efforts to prevent sexual deviance in students.